FITOREMEDIASI LIMBAH CAIR INDUSTRI TAPIOKA DENGAN TANAMAN ENCENG GONDOK - Muhammad Felani; Amir Hamzah (Universitas Tribhuwana Tunggadewi, 2007)
The objective of this study was to elucidate the possible phytoremediation of liquid waste of tapioca industry using Eichhornia crassipes prior its usage for watering maize grown on an Entisol of Malang. Tapioca liquid waste was mixed with pure water at various concentrations and then Eichhornia crassipes was grown on a water bath filled with the mixture. After twenty eight days, the mixture of tapioca liquid waste and pure water was analyzed for BOD, BOD, COD, DO, TSS, CN, total N, and total P, prior to its usage for watering maize grown on a pot filled with an Entisol. Results of this study showed that during twenty eight days Eichhornia crassipes grown on 25% tapioca liquid waste was capable to reduce BOD, COD, and CN concentrations of the liquid waste and to increase pH of the the mixture of liquid and pure water. This has resulted in a significant increase of maize growth